Essence of Criminal Law of the European Court of Human Rights - Timofieieva, Liliia (Teisė, 2022)
The Convention for the Protection of Human Rights and Fundamental Freedoms (the Convention) takes an important place in the doctrine and practice of criminal law of Ukraine and other countries. However, it could present some differences in interpretation of the provisions of the Convention in the Ukrainian legislation and in the practice of the European Court of Human Rights (ECHR). The aim of the article is to approximate national criminal law to international standards and the practice of the ECHR. The object of the article is essence of Criminal Law in the practice of the ECHR.